Optimization of the Profit of the Stock Portfolio Using Option Instruments - Rosický, Ondřej; Stádník, Bohumil; Drahokoupil, Jakub; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
Every retail investor faces the necessity of paying capital gain tax. This research builds on Aulerich (2011) and suggests the use of put and call options to avoid paying usually higher short-term capital gain tax and make the tax long-term. The retail investors can lock the profit by going long in the put option and short on the call option with the strike on the current spot price of the held stock. Base on the results this strategy can imporve significantly the after-tax returns by approximately the difference of short-term and long-term tax rate. Due to the contraints in the United States the strategy with put and call options is for tax purposes forbidden when the options are for same underlying stock used. Therefore use of correlated assets options is used as hedge instrument. The results show that even this strategy is better than selling stock and paying short-term capital gain. The desicion regarding of using the options or holding the stock long term is not clear. Strategy with options has lower return, but also lower risk, therefore, decision depends on the risk preference of each investor. Contrary, the use of S&P 500 index as underlying for hedge instrument is not better than selling the stock. The reason is that there is in many cases lack of correlation between the held stock and S&P 500. The mitigation of unsystematic risk in S&P 500 does not offset the lack of similar movement of price of index and held stock.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses